2012
DOI: 10.1007/s10162-012-0353-0
|View full text |Cite
|
Sign up to set email alerts
|

Quinoline Ring Derivatives Protect Against Aminoglycoside-Induced Hair Cell Death in the Zebrafish Lateral Line

Abstract: We have previously published results from a screen of 1,040 FDA-approved drugs and bioactives (NINDS Custom Collection) for drugs that protect against neomycin-induced hair cell death (Ou et al., J Assoc Res Otolaryngol 10:191-203, 2009). Further evaluation of this drug library identified eight protective drugs that shared a common quinoline scaffold. These drugs were tested further in terms of their protection against other aminoglycosides, as well as their effect on aminoglycoside uptake. All of the eight q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Previous work has demonstrated that quinoline drugs, including chloroquine, can 188 inhibit aminoglycoside ototoxicity by partially blocking mechanotransduction-dependent 189 toxin uptake (Ou et al, 2012). We reasoned that the asymptotic nature of the chloroquine 190 dose-response function might be due to its ability to block its own uptake.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Previous work has demonstrated that quinoline drugs, including chloroquine, can 188 inhibit aminoglycoside ototoxicity by partially blocking mechanotransduction-dependent 189 toxin uptake (Ou et al, 2012). We reasoned that the asymptotic nature of the chloroquine 190 dose-response function might be due to its ability to block its own uptake.…”
mentioning
confidence: 98%
“…The zebrafish lateral line is a good model for understanding hair cell function and 82 dysfunction (Harris et al, 2003;Ou et al, 2012;Pickett et al, 2018). The lateral line is a 83 system of mechanosensory hair cells on the surface of body that allows fish to detect fluid 84 displacement.…”
mentioning
confidence: 99%
“…Using established synthetic methods (31), we first chemically protected 3 of the amine groups on the aminoglycoside sisomicin, a biosynthetic precursor of gentamicin, thus allowing subsequent modification of the N1 and/or N3′′ amine site (Supplemental Figure 1, A and B; supplemental material available online with this article; doi:10.1172/JCI77424DS1). Sisomicin was selected because it is hair cell MET channel is required for drug toxicity (9,(20)(21)(22)(23), we have redesigned and modified the aminoglycoside sisomicin based on the biophysical properties of the hair cell MET channels (24) and aminoglycoside-bacterial ribosome interactions (25). Here, we have characterized 9 sisomicin derivatives with diminished ototoxicity in vitro, with 3 of the 9 compounds exhibiting comparable anti-E. coli activities to the parent compound sisomicin.…”
Section: Resultsmentioning
confidence: 99%
“…n = 2-9. jci.org Volume 125 Number 2 February 2015 bacterial activity. We modified the aminoglycoside compound based on the notion that hindering aminoglycoside entry via hair cell MET channel prevents ototoxicity (9,20). The design was based on the biophysical properties of the MET channel (24,26), whose candidate molecular compositions are still being elucidated (22,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Certain otoprotectants, namely those with quinolone rings, have been observed to confer protection by blocking aminoglycoside entry into hair cells instead of modulating cell death targets (Ou et al, 2009 , 2012 ). To test if Dihexa blocks aminoglycoside uptake by hair cells, we quantified GTTR fluorescence either with or without 1 μM Dihexa.…”
Section: Resultsmentioning
confidence: 99%